Migrant remittances and their impact on the economic development of the Baltic States - Rausser, Gordon; Strielkowski, Wadim; Bilan, Yuriy; Tsevukh, Yuliia (Geographica Pannonica, 2018)
This paper studies the determinants of international migration and remittances in the Baltic States (represented hereinafter by Lithuania, Latvia, and Estonia). The research reveals a critical view on migrant remittances in terms of macroeconomic development and social conditions in the society of each country involved into our research. In order to investigate and to demonstrate the impact of migrant remittances on GDP and consumption compared with current account balance, minimal wages, and foreign direct investment in the Baltic countries, econometric modeling based on the data of Eurostat, World Bank, and the National banks of the Baltic States has been employed. The results of this research clearly demonstrate that remittances sent by the migrants have high and positive impact on economic development in Lithuania, Latvia, and Estonia. Moreover, the findings stemming from this study confirm that minimum wages in the Latvia and Lithuania are far more important determinants of economic development than remittances.